2012
DOI: 10.2741/e496
|View full text |Cite
|
Sign up to set email alerts
|

Stress and its impact on farm animals

Abstract: Introduction 3. Impact of stress 3.1. Growth and production 3.2. Animal reproduction 3.3. Disease susceptibility 4. Indicators of stress 4.1. Behavioral changes 4.2. Hormonal indicators 4.3. Oxidative stress biomarkers 4.3.1. Quantification of oxidants and antioxidants 4.3.2. Estimation of the antioxidant enzymes and redox molecules 4.3.3. Measurement of oxidative damage4.4 Immunological markers 4.5 Genomic and Proteomic markers 5. Conclusions 6. References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 40 publications
0
49
0
3
Order By: Relevance
“…Cortisol, immune variables, and metabolic indicators in blood are the biomarkers most widely used to detect stress in both pigs and humans because the HPA axis, immune system, and metabolism are extremely sensitive to stress (33,34). In this study, blood cortisol significantly increased and maintained high levels in the ACTH group; blood immune variables were altered after ACTH administration, indicating that the immune system was activated.…”
Section: Discussionmentioning
confidence: 58%
“…Cortisol, immune variables, and metabolic indicators in blood are the biomarkers most widely used to detect stress in both pigs and humans because the HPA axis, immune system, and metabolism are extremely sensitive to stress (33,34). In this study, blood cortisol significantly increased and maintained high levels in the ACTH group; blood immune variables were altered after ACTH administration, indicating that the immune system was activated.…”
Section: Discussionmentioning
confidence: 58%
“…For example, the impacts of organic farming on eutrophication, but not biodiversity, have been studied in Sweden, although a large-scale meta-analysis has found positive effects of organic farming on biodiversity [115]. Studies have revealed a link between higher animal welfare and more disease resistant animals [116,117], indicating that interventions aimed at increasing animal welfare could also affect livestock epidemiology. A review focusing on the USA found positive effects of integrated animal and crop production on yield and profitability [118], which could potentially be true under Swedish market conditions as well.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that the SAM(sympathetic adrenal medullary system) is activated in response to a short-term or acute stress, its inability to rectify a stressful event results in the activation of the HPA axis (Lynch 2010), which, as mentioned earlier, is involved in resolving long-term, chronic stress (Kumar et al, 2012). Figure 2 illustrates the HPA axis pathway, associated hormones and target systems.…”
Section: Issn: 2319-7706 Volume 7 Number 07 (2018)mentioning
confidence: 99%
“…The HPA axis can be regarded as a crucial neuroendocrine system that is involved in the control of diverse physiological processes and adaptations to stress (Mormède et al, 2007). When the environmental pressure of a perceived stress exceeds that to which an animal"s adaptive mechanisms can accomodate (Kumar et al, 2012), this system produces energetic metabolites that arise either from energy storage tissues or from the transformation of proteins into energetic metabolites (Mormède et al, 2011). As such, HPA axis integrity and precise regulation of its function are essential characteristics of the successful adaptive response to any stressor.…”
Section: Hypothalamic-pituitary-adrenal (Hpa) Axismentioning
confidence: 99%
See 1 more Smart Citation